Bridging Salafi Tafsir and Modern Science: A Study of the Interaction of Religion and Science - Putra, Deden Juansa; Aminudin Shuib; Nurul Aulia; Farhan Suhada; Mufti Zevira (JIA (Jurnal Ilmu Agama), 2026)
This article aims to examine the interaction between the Salafi approach to religious interpretation and the development of modern science, focusing on their responses to the theory of evolution, cosmology, and other scientific phenomena. This study is motivated by the Salafi approach, which is known for its effort to preserve the purity of Islamic teachings through a literal understanding of the Qur'an and hadith. Using a qualitative method with an in-depth literature study of Salafi scholars’ writings, exegetical works, and academic sources, the data are analyzed through a thematic approach to understand the interaction with and responses to science within the Salafi doctrinal framework. The findings show that Salafi exegesis tends to adopt a selective stance toward modern science. They accept scientific theories or findings as long as they do not contradict textual evidence (dalil naqli), but reject ideas considered potentially harmful to Islamic creed or diminishing the purity of the textual meaning. This stance affirms the Salafi role in maintaining Islamic orthodoxy while simultaneously opening space for possible dialogue with the scientific community. Thus, the integration of religion and science from a Salafi perspective remains possible, provided that it is situated within a framework of respect for the sacred texts. Ultimately, this approach may serve as an important contribution to enriching mutual understanding amid the challenges of the modern era. This article contributes to the discourse on religion–science integration by positioning revelation as the primary epistemology. This model expands the typology of religion–science relations in Islamic studies and provides insight into the dynamics of Islamic orthodoxy in the modern era.